Modelo de negocio canvas en los emprendimientos de la Provincia de Los Ríos - Cruz Llamuca, Jomayra Jacqueline (2021)
The increase in entrepreneurship within the Province of Los Ríos, means that business models have become a fundamental instrument, since they involve elements that influence the business and the market, as well as a starting point to create initiatives of innovation and thus be able to obtain notoriety of the company through content marketing and networks. The Canvas business model is an instrument that supports the deployment of adequate skills for businesses or entrepreneurs to generate value. The objective of the case study is to present the Canvas business model as a successful business model before starting the management of the digital marketing segment, together with the Canva software in the enterprises within the Province of Los Ríos, presenting as four success stories in which it is; Abc Technology, Fuente De Papel, Vitae Express Quevedo, Bohemian Style through the use of this methodology and website. The methodology carried out in the research was qualitative, since only one interview and observation sheet were carried out, filling them, not probabilistic, and the size of the sample was from a group of entrepreneurs from the Province of Los Ríos. The results showed the feasibility of the project, which is why it is concluded that the Canvas business model is an effective tool in the structuring of business models, since it considers all the necessary key aspects of a business, likewise the Canva software is an Free design tool with essential tools to successfully manage and create quality content. Likewise, the incidence and influence of the networks within each of the undertakings was seen.